A randomised test of printed educational materials about melanoma detection: Varying skin self-examination technique and visual image dose. (November 2015) - King, Andy J; Carcioppolo, Nick; Grossman, Douglas; John, Kevin K; Jensen, Jakob D
Objective: Melanoma incidence and mortality rates continue to rise globally, making it essential for researchers to identify effective approaches to disseminating information to the public that improve key outcomes. This study compared two skin self-examination (SSE) educational strategies: the ABCDE (asymmetry, border irregularity, multiple colours, diameter greater than 6 mm and evolution over time) approach and the ugly duckling sign (UDS). Design: A randomised experiment testing different presentations of SSE techniques and visual image dose. Setting: The experiment took place at a shopping centre in the Midwest USA. Method: Participants ( N  = 301) participated in the study in which they viewed brochures featuring one of two SSE training methods, ABCDE or UDS, along with a low, moderate or high dosage (frequency) of visual images. Results: The brochures improved willingness to perform SSE and skin cancer knowledge across all groups, with brochures featuring the UDS increasing willingness to perform SSE as visual image dose increased. Sensitivity and specificity outcomes were similar across all groups, with a slight advantage found for displaying a moderate visual image dose visualising the ABCDE condition (sensitivity = .63, specificity = .79). Conclusions: Overall, both the ABCDE and UDS approaches demonstrated utility in improving early skin cancer detection and education. A balanced presentation of typical and atypical nevi images seems to be an important consideration when presenting visual and written information about melanoma to laypersons.